2018
DOI: 10.3765/plsa.v3i1.4333
|View full text |Cite
|
Sign up to set email alerts
|

The influence of language background and exposure on phonetic accommodation

Abstract: This study examines whether language background, short-term exposure to monolingual and bilingual speech, and long-term exposure to monolingual and bilingual speech influences speech accommodation. To address this question, I examine whether English monolinguals and Spanish-English bilinguals, either from a predominately monolingual community or a predominately bilingual community, vary their speech when interacting with a monolingual English speaker versus a Spanish-English bilingual speaker. Additionally, I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…This inference was triggered in this case by the interlocutor's syntactic behaviour, which in turn elicited different patterns of adaptation in the context of speaking to a native or a nonnative interlocutor. This finding complements results from a small but growing body of work highlighting the role of socioperceptual factors on phonetic (Kim et al, 2011;Enzinna, 2018) and syntactic (Weatherholtz et al, 2014;Balcetis & Dale, 2005) adaptation. Our results however are not fully consistent with Weatherholtz et al, who found a mediating effect of perceived political affinity on the degree of PO/DO adaptation, but no evidence of divergence from a speaker of a different political orientation.…”
Section: Discussionsupporting
confidence: 84%
“…This inference was triggered in this case by the interlocutor's syntactic behaviour, which in turn elicited different patterns of adaptation in the context of speaking to a native or a nonnative interlocutor. This finding complements results from a small but growing body of work highlighting the role of socioperceptual factors on phonetic (Kim et al, 2011;Enzinna, 2018) and syntactic (Weatherholtz et al, 2014;Balcetis & Dale, 2005) adaptation. Our results however are not fully consistent with Weatherholtz et al, who found a mediating effect of perceived political affinity on the degree of PO/DO adaptation, but no evidence of divergence from a speaker of a different political orientation.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies of L2 speech accommodation have shown that L2 speakers are able to accommodate toward native speakers in both shadowing tasks and spontaneous conversations (Althubyani, 2021; Cao, 2015; Chang, 2013; Enzinna, 2018; Hao & de Jong, 2016; Jia et al, 2006; Jiang & Kennison, 2022; Kim et al, 2011; Law et al, 2020; Lewandowski, 2012; Lewandowski & Jilka, 2019; Liu, 2017; Olmstead et al, 2021; Tobin, 2022; Tobin et al, 2018; Young, 1988; Zajac & Rojczyk, 2014). Among these studies, Kim et al (2011), Tobin (2022), Jia et al (2006), and Hao and de Jong (2016) are reviewed here, owing to their high relevance to the current project.…”
Section: Speech Accommodation Of L2 Speakersmentioning
confidence: 99%
“…So far, only a handful of studies have taken individual differences in L2 accommodation into consideration (Althubyani, 2021; Lewandowski, 2012; Lewandowski & Jilka, 2019; Reiterer et al, 2013; Yu et al, 2013; Zellou, 2017): many studies tend to treat L2 speakers as a group of participants with a homogeneous accent. In L2 accommodation, some studies distinguish L2 speakers by their language experience (Chang, 2013; Enzinna, 2018). For example, Chang (2013) examined both experienced and inexperienced English learners of Korean in the USA and found that experienced learners changed less in their L1 than inexperienced learners.…”
Section: Speech Accommodation Of L2 Speakersmentioning
confidence: 99%
See 1 more Smart Citation